Stereotipe, Prasangka dan Dinamika Antaretnik - Ilyas Lampe; Haslinda B. Anriani (Balai Pengembangan SDM dan Penelitian Komunikasi dan Informatika (BPSDMP Kominfo) Banjarmasin, 2016)
Ethnic identity is a differentiator that is primordial that is often used to establish an association to a particular group, as ingroup or outgroup that in the local context the plural is called the